Propriedades de transporte em óxidos condutores transparentes (TCOs): In2O3, SnO2 e SnO2:F - Amorim, Cleber Alexandre de (Universidade Federal de São Carlos, 2014)
In this work we studied some of the structural features and transport in nanostructured metal oxides synthesized by the vapor -solid mechanism (VS) aiming their application in high performance devices. The structural properties of the used samples [In2O3, SnO2 and SnO2 doped with fluorine (FTO)] were characterized by X-ray diffraction, scanning electron microscopy (SEM) and X- ray dispersive energy spectroscopy (EDX). All these techniques confirmed the monocrystalline character which was obtained by the method used for the synthesis process. Concerning the electronic transport properties, a common property for all samples was detected: the conduction mechanism was the variable range hopping. Invariably, such as mechanism is attributed to the presence of a small degree of electronic disorder in samples but which is not enough to induce the localization of all carriers. As an observable result, samples behaved as semiconductors. Specifically, in In2O3 samples the analysis of temperature dependent resistivity allowed us to determine parameters such as the localization length, also determining the dimensionality of the electronic system. Although not intentionally doped, the samples exhibited an appreciable density of electrons due to the amount of oxygen vacancies. Experiments performed with micro-sized sample, unpublished in literature, provided data on mobility and carrier density and their dependence on temperature, determining the dominant scattering process: for ionized impurities (low temperature) and acoustic phonon (high temperatures). The used approach avoids common errors in extraction of those kinetic parameters using devices like field effect transistors, serving as a versatile platform for the direct investigation of electronic properties in nanoscale materials. Samples of SnO2, monocrystalline and not intentionally doped (but with a little influence of oxygen vacancies) also showed a semiconducting behavior guided by the hopping mechanism in a wide temperature range (60-300 K). The presence of a potential barrier in the samples surface lead us to a detailed analysis of the performance metal-semiconductor (SnO2) junctions which was performed using different approaches: thermionic emission , statistical (Gaussian) distribution of Schottky barriers and a double Schottky barrier model. From these, we obtained a fairly detailed description of system providing parameters such as the barrier height (0B ~ 0,42 eV) and the ideality factor (n ~ 1, 05) comparable to the values obtained under conditions of ultra- high vacuum. These samples were used in field effect transistors that exhibited interesting characteristics for applications such as mobility of 137 cm2/Vs. Finally, FTO samples in which we could act on the doping level were explored. Samples showed a monocrystalline character and again a semiconductor behavior was evidenced by the hopping conduction mechanism. With the introduction of dopants on oxygen sites, devices showed an additional effect when a dispersion of nanobelts was used: a negative temperature resistivity coefficient for T < 15 K. We show that this behavior fits in the theory of weak localization in a system of weak disorder. Devices with a single nanobelt has a much smaller chance to exhibit the same behavior as a function of its dimensions. This result is general as suggested by the data: only the intrinsic disorder contributes to the transport mechanism, while the extrinsic one (the dispersion of nanobelts) not contributes. Finally, field effect transistors were constructed showing better mobility parameters for applications. Another original contribution of this work was the determination of an intrinsic parameter for the different materials which is only estimated by theoretical calculations in the literature: the density of states which should be used as reference in literature.
Keywords: Física da matéria condensada; Nanofios semicondutores; Óxido de estanho; Caracterização elétrica; Transporte eletrônico; CIENCIAS EXATAS E DA TERRA::FISICA